Effects of Anti-Obesity Strategies on Bone Mineral Density: A Comprehensive Meta-Analysis of Randomized Controlled Trials - Myung Jin Kim; Seonok Kim; Han Na Jung; Chang Hee Jung; Woo Je Lee; Yun Kyung Cho (Journal of Obesity & Metabolic Syndrome)
Background : Although an appropriate weight management strategy is essential for obese individuals, weight loss can have adverse effects on bone mineral density (BMD). We conducted a systematic review of randomized controlled trials to evaluate changes in BMD after the implementation of various weight loss strategies. Methods : The PubMed, Embase, Web of Science, and Cochrane Library databases were searched to find articles published from database inception until June 2023. Randomized controlled trials of various treatments for obese patients that reported changes in BMD were selected. The primary outcome was BMD of the whole body, lumbar spine, and total hip, measured using dual X-ray absorptiometry. Results : Eighteen randomized controlled trials involving 2,510 participants with obesity were included in the analysis. At follow-up examination, the BMD of the lumbar spine decreased significantly after metabolic surgery (mean difference [MD]=-0.40 g/cm2; 95% confidence interval [CI], -0.73 to -0.07; I2=0%); lifestyle and pharmacological interventions did not result in a significant decrease in BMD at any location. Metabolic surgery also produced the most substantial difference in weight, with an MD of -3.14 (95% CI, -3.82 to -2.47). Conclusion : This meta-analysis is the first to examine the effects of all categories of anti-obesity strategies, including the use of anti-obesity medications, on BMD. Bariatric metabolic surgery can have adverse effects on BMD. Moreover, medications can be used as a treatment for weight loss without compromising bone quality.